Exploring satisfaction of amusement parks in Indonesia - Ardhitama Shaumarli; Radiani Nurwitasari (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
The rapid growth of amusement parks in Indonesia has elevated them to significant tourist hubs, prompting a detailed examination of visitor satisfaction within these settings. This study aims to analyze the satisfaction trends among tourists visiting the top 11 amusement parks in Indonesia and assess whether their ratings accurately reflect their satisfaction. Moreover, it investigates the factors influencing satisfaction levels, employing an adjusted rating method to dissect tourists' ratings and compare them with sentiment analysis results derived from provided reviews. While acknowledging the fluctuating performance of these destinations, with most showing signs of improvement, the study highlights that only 5 destinations within the sample exhibit comovement between adjusted ratings and sentiment analysis results. Furthermore, a closer inspection reveals that some destinations have successfully minimized the prevalence of negative sentiments expressed in reviews. However, there is still 1 destination that is of concern because it has decreased customer satisfaction as indicated by a decrease in score and the addition of negative sentiment.